Global burden of subarachnoid hemorrhage attributable to ambient PM2.5 in low-resource regions (1990–2050) - Wu, Erman; Tang, Tong; Su, Riqing; Li, Yandong; Mijiti, Maimaitili; Zhang, Gaocai; Lian, Minghao; Zhang, Yongtao; Du, Chang; Zhu, Guohua; Geng, Dangmurenjiafu (Frontiers in Public Health, 2025)
BackgroundSubarachnoid hemorrhage (SAH) is increasingly recognized as a PM2.5-linked neurological emergency, yet global spatiotemporal burden evidence across socioeconomic, demographic, and geographic subgroups remains scarce, impeding tarsgeted prevention. This study quantifies current burden, trends, and future SAH projections attributable to PM2.5 using the latest data.MethodsUsing data from the Global Burden of Disease Study 2021, we analyzed deaths and disability-adjusted life years (DALYs) from SAH attributable to ambient PM2.5 pollution (1990–2021) across 204 countries/territories, stratified by age, sex, region, and Socio-demographic Index (SDI). Temporal trends were quantified using estimated annual percentage changes (EAPCs), and Bayesian age-period-cohort modeling projected disease burden through 2050.ResultsBetween 1990 and 2021, global age-standardized mortality (ASMR) and DALY rates (ASDR) for PM2.5-related SAH declined by 36% (0.99 to 0.63 per 100,000) and 34% (27.42 to 17.96 per 100,000), respectively. However, absolute deaths surged 40% (38,130 to 53,562), driven by aging populations and demographic shifts. Burden disparities were stark: Middle SDI regions had the highest ASMR (1.07, 95% UI, 0.68–1.43) and ASDR (27.42, 95% UI: 17.96–35.65), while high SDI regions achieved the steepest declines (−67% ASMR). South Asia (+246% deaths) and Southeast Asia (+147% deaths) experienced the most rapid mortality growth, contrasting with East Asia’s high absolute burden (229,553 deaths in 2021). Males faced higher risks (ASMR: 0.72, 95% UI: 0.48–0.99) compared with females (0.55, 95% UI: 0.36–0.75). In South Asia, the female mortality share was rising from 31 to 41%. Mongolia had the highest national burden [2.49 (95% UI, 1.23–3.82) and ASDR of 61.92 (95% UI, 30.6–93.24)], while Central Asia and Southern Sub-Saharan Africa exhibited worsening trends. Projections indicate a resurgence in ASMR and ASDR by 2050, disproportionately impacting low-middle SDI regions.ConclusionDespite declining age-standardized rates, a 40% surge in absolute PM2.5-attributable SAH deaths over three decades, due to aging populations and regional inequalities (e.g., South Asia +246% deaths, Middle SDI highest ASMR), demands urgent air-quality and healthcare policies for high-growth Asian and African regions and vulnerable low-middle SDI populations to curb projected 2050 increases.